2002
DOI: 10.1002/clc.4960250303
|View full text |Cite
|
Sign up to set email alerts
|

Measuring treatment effects of Cilostazol on clinical trial endpoints in patients with intermittent claudication

Abstract: Summary: Intermittent claudication (IC) comprises the most common presenting symptoms of peripheral arterial disease (PAD), which itself is a manifestation of systemic atherosclerosis. Typical symptoms of IC are aching pain, numbness, and fatigue in the lower extremities. Symptoms are induced by walking or exercise and usually resolve with rest. The cornerstone of treating IC is risk-factor reduction and a supervised exercise regimen. Pharmacotherapy specifically indicated for the treatment of IC includes a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It has already been shown that the PDE3 inhibitor cilostazol (an analogue of cilostamide) is an effective drug for the clinical treatment of symptoms of intermittent claudication due to peripheral arterial disease, which itself, is believed to be a manifestation of systemic atherosclerosis. 30 It has also been reported that PDE3 activity and expression are significantly increased in the aorta of atherosclerosis-prone insulin-resistant rats. 31 Together these findings indicate that PDE3 may play an important role in vascular diseases such as atherosclerosis and therefore suggest that PDE3 inhibitors may be therapeutically useful for the treatment and prevention of atherosclerosis.…”
Section: Discussionmentioning
confidence: 96%
“…It has already been shown that the PDE3 inhibitor cilostazol (an analogue of cilostamide) is an effective drug for the clinical treatment of symptoms of intermittent claudication due to peripheral arterial disease, which itself, is believed to be a manifestation of systemic atherosclerosis. 30 It has also been reported that PDE3 activity and expression are significantly increased in the aorta of atherosclerosis-prone insulin-resistant rats. 31 Together these findings indicate that PDE3 may play an important role in vascular diseases such as atherosclerosis and therefore suggest that PDE3 inhibitors may be therapeutically useful for the treatment and prevention of atherosclerosis.…”
Section: Discussionmentioning
confidence: 96%
“…A phase 2 trial with cilostazol in patients with MCI (NCT02491268) started in 2015 with an expected completion date of December 1, 2020 but results have not been posted on ClinicalTrials.gov. In a retrospective study, treatment with cilostazol was associated with slowing of cognitive decline in MCI patients but not AD patients [449] while in another retrospective study cilostazol slowed the decrease in MMSE scores in patients with mild dementia but not moderate-to-severe dementia (type of dementia not [445], prevention of deep vein thrombosis after knee or hip replacement surgery [446] Chitin Tissue engineering, wound dressing, drug delivery, cancer diagnosis [447], cancer treatment (used as vehicle for drug delivery [448] Cilostazol MCI a [449], AD b [450], prevention of restenosis and repeat revascularization after percutaneous coronary intervention [451], prevention of vascular mortality and cardiovascular events in patients with stable intermittent claudication [452], ischemic leg ulcers, chronic arterial occlusion, prevention of recurrence of cerebral infarction, chronic atrial fibrillation with episodes of bradycardia [453], prevention of stroke recurrence (NCT00202020), fatty liver disease (NCT04761848), prevention of peripheral neuropathy (NCT05298696), lower extremity revascularization (NCT02374957), Reynaud's (NCT00048776), recurrent stroke with intracranial artery stenosis (NCT00333164)…”
Section: -Caffeoylquinic Acidmentioning
confidence: 99%
“…The result is an increase in cAMP concentrations in blood vessels and platelets, inducing peripheral vasodilaton and inhibiting platelet aggregation. Cilostazol has also been shown to reduce triglycerides and increase high‐density lipoproteins (HDL cholesterol) …”
Section: Introductionmentioning
confidence: 99%